Equivalence, Justice, Injustice – Health and Social Care Decision Making in Relation to Prison Populations - Shepherd, Andrew; Hewson, Tom; Hard, Jake; Green, Russell; Shaw, Jennifer (Frontiers in Sociology, 2021)
Prisons represent sites of singular healthcare need – characterised by high levels of distress and disorder. In many jurisdictions, practitioners are ethically charged with delivering healthcare that is “equivalent” to that available in the wider community. This claim has been much debated – yet the emergence of a global coronavirus pandemic has highlighted the arguments in a particularly stark manner. In the following conceptual analysis, we explore the emergent discourse of the coronavirus and consider its particular significance for prison healthcare decision making and the concept of equivalence. For example, both the coronavirus pandemic and practice of prison incarceration induce a sense of varied temporality: The discourse of prison is replete in this area – such as the concept of “hard time.” Alongside this, the discourse in relation to coronavirus has highlighted two competing modes of temporal understanding: The political – where the pandemic is conceptualised as has having a discrete “beginning and end”, and the scientific - where the “new normal” reflects the incorporation of the “novel” coronavirus into the wider ecology. The impact of these disparate understandings on the prison population is complex: “Locking down” prisoners – to safeguard the vulnerable against infection – is relatively simple, yet it has traumatic repercussions with respect to liberty and psychosocial health. Easing lockdown, by contrast, is a difficult endeavour and risks collision between the temporalities of prison – where “hard time” is accentuated by separation from the “real world” – the political and the scientific. Whither then the concept of equivalence in relation to a field that is definitively non-equivalent? How can practitioners and policy makers maintain a just ethical stance in relation to the allocation of resources when it comes to a politically marginalised yet manifestly vulnerable population? We argue that further debate and consideration are required in this field – and propose a framework for such discussion.